Migrants and Expats: The Swiss Migration and Mobility Nexus - Steiner, Ilka; Wanner, Philippe (IMISCOE Research Series, 2019)
This open access book provides insight on current patterns of migration in Switzerland, which fall along a continuum from long-term and permanent to more temporary and fluid. These patterns are shaped by the interplay of legal norms, economic drivers and societal factors. The various dimensions of this Migration-Mobility Nexus are investigated by means of newly collected survey data: the Migration-Mobility Survey. The book covers different aspects of life in the host country, including the family dimension, the labour market and political participation as well as social integration. The book also takes into account the chronological dimension of migration by considering the migrants' arrival, their stay, and their expectations regarding return. Through applying conclusions drawn from the Swiss context to the migration literature on other European and high-income countries, this book contributes to new knowledge on current migration processes in high-income countries. As such it will be a valuable reference work to scholars and students in migration, social scientists and policy makers.